A Transmembrane Form of the Prion Protein Contains an Uncleaved Signal Peptide and Is Retained in the Endoplasmic Reticululm - Stewart, Richard S. (The American Society for Cell Biology, 2001)
Although there is considerable evidence that PrP(Sc) is the infectious form of the prion protein, it has recently been proposed that a transmembrane variant called (Ctm)PrP is the direct cause of prion-associated neurodegeneration. We report here, using a mutant form of PrP that is synthesized exclusively with the (Ctm)PrP topology, that (Ctm)PrP is retained in the endoplasmic reticulum and is degraded by the proteasome. We also demonstrate that (Ctm)PrP contains an uncleaved, N-terminal signal peptide as well as a C-terminal glycolipid anchor. These results provide insight into general mechanisms that control the topology of membrane proteins during their synthesis in the endoplasmic reticulum, and they also suggest possible cellular pathways by which (Ctm)PrP may cause disease.